VD_FINDINFO HC / 2011 / 267 vom 13. Mai 2011 - VD Tribunal cantonal (2011)
RÉSILIATION IMMÉDIATE, PROTECTION DE LA PERSONNALITÉ, TORT MORAL | 328 CO, 337c al. 1 CO, 337c al. 2 CO, 337c al. 3 CO, 60 LPers-VD